The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1007/s13280-014-0578-8
|View full text |Cite
|
Sign up to set email alerts
|

Managing water services in tropical regions: From land cover proxies to hydrologic fluxes

Abstract: Watershed investment programs frequently use land cover as a proxy for water-based ecosystem services, an approach based on assumed relationships between land cover and hydrologic outcomes. Water flows are rarely quantified, and unanticipated results are common, suggesting land cover alone is not a reliable proxy for water services. We argue that managing key hydrologic fluxes at the site of intervention is more effective than promoting particular land-cover types. Moving beyond land cover proxies to a focus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 41 publications
(42 reference statements)
1
38
0
Order By: Relevance
“…The effects of vegetation on water supply are more pronounced in water-limited regions than water unlimited (energy-limited) regions ). For example, deforestation in areas with precipitation formation dominated by cloud could reduce interception of precipitation and thus reduce streamflow (Ponette-Gonzalez et al 2015). In a special case, extensive deforestation in snow-dominated Northern Angara region in Russia caused a deceased in river flow by about 10-20 mm over the first two decades following clearcutting the deciduous forests (Onuchin et al 2017).…”
Section: Water Cycle and Supplymentioning
confidence: 99%
“…The effects of vegetation on water supply are more pronounced in water-limited regions than water unlimited (energy-limited) regions ). For example, deforestation in areas with precipitation formation dominated by cloud could reduce interception of precipitation and thus reduce streamflow (Ponette-Gonzalez et al 2015). In a special case, extensive deforestation in snow-dominated Northern Angara region in Russia caused a deceased in river flow by about 10-20 mm over the first two decades following clearcutting the deciduous forests (Onuchin et al 2017).…”
Section: Water Cycle and Supplymentioning
confidence: 99%
“…Thus, we focused our project on comparing groundwater recharge under different types of land cover . Because recharge can occur under forest, grassland, or even in drywells in an urbanized area, it was crucial to explicitly and specifically identify plausible future land‐cover types in order to produce informative findings …”
Section: Characteristics Of the Hydrologic Services Approachmentioning
confidence: 99%
“…Also of note, we found that in some cases, a land transition that increased water availability simultaneously increased the provision of other ecosystem services but that ecosystem services did not consistently rise and fall together. This highlights the importance of evaluating synergies and trade‐offs among ecosystem services relative to specific land‐use transitions …”
Section: Characteristics Of the Hydrologic Services Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…While this overcomes many of the problems of monitoring and enforcement identified above, it also makes it difficult to ascertain whether water resources are actually being improved (Peñuela-Arévalo and Carrillo-Rivera, 2012). Designing programs appropriate to the specific hydrogeologic setting should help ensure desired impacts (Ponette-González et al, 2014). Concerns have been raised about the equity (Leimona et al, 2015) and sustainability (Klöve et al, 2011) implications of relying on a marketbased mechanism to enhance water resources.…”
Section: Market Instrumentsmentioning
confidence: 99%